Depression comorbidity in spinocerebellar ataxia - Schmitz-Hübsch, Tanja; Coudert, Mathieu; Tezenas du Montcel, Sophie; Giunti, Paola; Labrum, Robyn; Dürr, Alexandra; Ribai, Pascale; Charles, Perrine; Linnemann, Christoph; Schöls, Ludger; Rakowicz, Maryla; Rola, Rafal; et al. (Movement disorders, 2011)
This is a description of the prevalence and profile of depressive symptoms in dominant spinocerebellar ataxia (SCA). Depressive symptoms were assessed in a convenience sample of 526 genetically confirmed and clinically affected patients (117 SCA1, 163 SCA2, 139 SCA3, and 107 SCA6) using the Patient Health Questionnaire (PHQ). In addition, depressive status according to the examiner and the use of antidepressants was recorded. Depression self-assessment was compared with an interview-based psychiatric assessment in a subset of 26 patients. Depression prevalence estimates were 17.1% according to the PHQ algorithm and 15.4% when assessed clinically. The sensitivity of clinical impression compared with PHQ classification was low (0.35), whereas diagnostic accuracy of PHQ compared with psychiatric interview in the subset was high. Antidepressants were used by 17.7% of patients and in >10% of patients without current clinically relevant depressive symptoms. Depression profile in SCA did not differ from a sample of patients with major depressive disorder except for the movement-related item. Neither depression prevalence nor use of antidepressants differed between genetic subtypes, with only sleep disturbance more common in SCA3. In a multivariate analysis, ataxia severity and female sex independently predicted depressive status in SCA. The PHQ algorithmic classification is appropriate for use in SCA but should stimulate further psychiatric evaluation if depression is indicated. Despite a higher risk for depression with more severe disease, the relation of depressive symptoms to SCA neurodegeneration remains to be shown. © 2011 Movement Disorder Society